PENDIDIKAN ISLAM DI TENGAH MASYARAKAT MULTIKULTURAL - Nurfadilah (Al'Adalah, 2016)
Indonesia is one of the largest multicultural countries in this world. It can be proven by the wide and kind of the condition of socio cultural or geography, moreover it has many religions and faiths that exist in this country, such as Islam, Christian Catholic, Protestant, Hindu, Buddhist, and Konghucu, as well as varieties of faiths which resects each conviction without tolerate other people’s belief, so it is not suitable with the symbol of the country that is different remain one. If it is analyzed deeply, Islam is very kind and respects the diversity as reality (natural law – sunnat Allah). In this case, the concept of rahmatan lil ‘alamin is the cultural basis of Islam. For carrying out the humani-ty’s mission, Islam has an instrument that is put the education in front, since education face the human directly. Education is a container which serves to humanize in order to be a perfect man. Education, culture, and society is the unity that has an important role in creating insan kamil. The society is a per-son who is able to serve facilities and infrastructure which is going to pro-duce the culture, while education is a process to preserve and develop the values which attach life in society.